Liver Organoids: Recent Developments, Limitations and Potential - Harrison, Sean Philip; Baumgarten, Saphira Felicitas; Verma, Rajneesh; Lunov, Oleg; Dejneka, Alexandr; Sullivan, Gareth John (Frontiers in Medicine, 2021)
development, toxicity, as well as genetic and infectious disease in ways currently limited by the availability of primary tissue. With the added advantage of patient specificity, which can play a role in all of these areas. Many iPSC differentiation protocols focus on 3 dimensional (3D) or organotypic differentiation, as these offer the advantage of more closely mimicking in vivo systems including; the formation of tissue like architecture and interactions / crosstalk between different cell types. Ultimately such models have the potential to be used clinically and either with or more aptly, in place of animal models. Along with the development of organotypic and micro-tissue models, there will be a need to co-develop imaging technologies to enable the visualisation of these evolving models. A variety of liver models termed “organoids” have been reported in the literature ranging from simple spheres or cysts of a single cell type, usually hepatocytes, to those containing multiple cell types combined during the differentiation process such as hepatic stellate cells, endothelial cells and mesenchymal cells, often leading to an improved hepatic phenotype. These allow specific functions or readouts to be examined such as drug metabolism, protein secretion or an improved phenotype, but because of their relative simplicity they lack the flexibility and general applicability of ex vivo tissue culture. In the liver field these are more often constructed rather than developed together organotypically as seen in other organoid models such as brain, kidney, lung and intestine. Having access to organotypic liver like surrogates containing multiple cell types with in vivo like interactions / architecture, would provide vastly improved models for disease, toxicity and drug development, combining disciplines such as microfluidic chip technology with organoids and ultimately paving the way to new therapies.